THE EFFECT OF CAPITAL STRUCTURE, PROFITABILITY, AND FIRM SIZE ON FIRM VALUE(A Study of Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period) - Perwi Pandapotan Manik; Nyoman Triaryati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to analyze the effect of capital structure, profitability, and firm size on firm value in property and real estate sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Firm value is proxied by Price to Book Value (PBV), capital structure is measured using the Debt to Equity Ratio (DER), profitability is measured using Return on Equity (ROE), and firm size is measured by the natural logarithm of total assets. This research employs a quantitative approach using secondary data derived from companies’ financial statements. The sample was determined using a purposive sampling technique, resulting in 58 companies with a total of 290 observations. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26, after fulfilling the classical assumption tests. The results indicate that capital structure, profitability, and firm size simultaneously have a significant effect on firm value. Partially, all three variables are proven to have a positive and significant effect on firm value. These findings suggest that optimal capital structure management, high profitability, and larger firm size serve as positive signals for investors in assessing company performance and future prospects, thereby increasing firm market value. The research model is able to explain 70.3% of the variation in firm value, while the remaining is influenced by other factors outside the model. This study supports signaling theory, which states that financing decisions, profitability, and firm size reflect important information for investors regarding company stability and growth prospects. The results are expected to provide consideration for management in formulating financial strategies and for investors in making investment decisions in the property and real estate sector.